Analysis of the Impact of Serpong-Balaraja Toll Road Development on Changes in Social and Economic Conditions of the Kadusirung Village Community, Tangerang Regency - Deva Erlangga; Winarno Winarno (JPG (Jurnal Pendidikan Geografi), 2023)
The construction of the Serpong-Balaraja toll road is one of the national development programs aimed at reviving the country's economy, by connecting one region with another so as to accelerate the pace of economic development of the area through which it passes. However, this development has resulted in changes to the geographical conditions in Kadusirung Village, Pagedangan Subdistrict, Tangerang Regency. These changes in geographical conditions can affect changes in the social and economic conditions of the people who live around the toll road construction area. The purpose of this study was to determine the impact of the Serpong-Balaraja toll road development on changes in the social and economic conditions of the community in Kadusirung Village, Pagedangan Subdistrict, Tangerang Regency. This type of research is descriptive qualitative. The sampling method using purposive sampling technique amounted to 85 respondents consisting of local government officials, traders, and other communities adjacent to the toll road construction area. The research used primary and secondary data. The data collection techniques used were interviews, observation and documentation. The data analysis technique uses qualitative descriptive analysis.Â The results showed that social relations have changed, with 73% thinking that they are less harmonious. As much as 85% of community participation in community service has decreased. And 94% of respondents thought that accessibility had become more difficult. Meanwhile, the average land area decreased by 20.6%. the type of work changed by 1%. Income decreased by 2.4%. and expenditure increased by 1.1%. this had an impact on changing social interaction relationships in the study area to be more individual than before, and affected some people's income, especially those who earned income as traders and laborers